TRANSFORMASI PERSONAL: DARI KEJAHATAN MENUJU KESALEHAN - Gazi Saloom (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This study investigates how and why the personal transformation occurred in former convicts in Indonesia. This study employs a qualitative approach with in-depth interviews and review of documents including social media as data collection instruments. Two former convicts serve as the research subjects, while five people among ex convicts’ family and friends serve as the research informants. To provide the study credibility, triangulation of data and resources was conducted, namely by examining data obtained from social media like YouTube that displays personal experiences some ex criminals who have transformed. Data were analyzed by using thematic analysis technique. The results showed that the process of personal transformation occurred throughout a long stage and did not occur shortly. It was also found that the personal factor (e.g. the understanding of personal experiences and social factors, especially intensive and prolonged interaction with religious leaders) was the main drive for personal change. The theoretical implications of these results were also discussed. KEY WORDS: Personal, transformation, experiences, contact